Thermosetting resin for fixing electronic component and preparation process thereof

A modified cyanate ester resin with a three-dimensional network aluminum nitride filler and surface treatment addresses thermal conductivity and mechanical property challenges, achieving efficient heat conduction and superior mechanical performance for electronic components.

CN119192837AActive Publication Date: 2024-12-27HUNAN NAGE NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411719080.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-27
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Cyanate ester resins exhibit insufficient thermal conductivity, which restricts their application in modern electronic products, and modifying them with thermally conductive fillers like graphene and carbon nanotubes faces challenges such as dispersion issues, increased processing difficulty, reduced fluidity, and compromised mechanical properties.

Method used

A thermosetting resin is formulated with modified cyanate resin, surface-modified three-dimensional network aluminum nitride thermal conductive filler, and a curing agent, optimized by fluorine-containing and silicon-containing organic compounds to enhance thermal conductivity and mechanical properties. The filler is composed of micron-scale whiskers and nanometer-scale nanowires with a divergent structure, and surface modification with γ-glycidyloxypropyltrimethoxysilane and sodium oxalate or sodium succinate improves compatibility and crystallization.

Benefits of technology

The modified resin achieves enhanced thermal conductivity and mechanical properties, suitable for electronic packaging, with improved hardness, durability, and toughness, forming efficient heat conduction channels and pathways.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192837A_ABST
    Figure CN119192837A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermosetting resin materials, and provides thermosetting resin for fixing an electronic component and a preparation process thereof, and the thermosetting resin for fixing the electronic component comprises the following components in parts by weight: 50-75 parts of modified cyanate ester resin, 10-30 parts of surface modified three-dimensional reticular aluminum nitride heat-conducting filler and 3-8 parts of a curing agent; three-dimensional reticular aluminum nitride is used as a heat-conducting filler, so that a rapid heat-conducting channel can be formed in the resin, and the heat conductivity is improved; meanwhile, modification of the surface of the aluminum nitride, formation of microcrystals in the cyanate ester resin and optimization of a microstructure are synchronously carried out, so that the heat-conducting property and the mechanical property are further enhanced, and the prepared thermosetting resin shows excellent mechanical and heat-conducting properties and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermosetting resin materials, and in particular to a thermosetting resin for fixing electronic components and a preparation process thereof. Background Art

[0002] Cyanate ester resin is a high-performance thermosetting resin. Its cured form exhibits excellent heat resistance. Cyanate ester resins are highly stable in high-temperature environments, are not susceptible to moisture or thermal degradation, exhibit extremely low hygroscopicity, and possess excellent dimensional stability. Furthermore, these resins exhibit excellent dielectric properties, with dielectric constants and dielectric losses remaining low over a wide frequency band and temperature range. These excellent properties have led to their widespread use in electronic packaging. However, cyanate ester resins also have limitations. Their low thermal conductivity has, to some extent, restricted their application in modern electronic products.

[0003] In order to improve its thermal conductivity, a common method is to add thermally conductive fillers such as silicon dioxide, boron nitride, graphene, etc. to cyanate ester resin. These fillers have higher thermal conductivity and can effectively conduct heat, thereby improving the thermal conductivity of cyanate ester resin. However, there are the following shortcomings. For example, the Chinese patent application with the authorization notice number CN104231624B discloses a modified cyanate ester resin thermal conductive composite material and a preparation method thereof. The cyanate ester resin is modified with graphene and carbon nanotubes. Although there is a certain improvement in thermal conductivity, graphene and carbon nanotubes are difficult to disperse in the matrix, and graphene and carbon nanotubes are diffusely distributed, making it difficult to form a thermal conductive network in the cyanate ester resin. Therefore, the thermal conductivity still has certain limitations. Improving the crystallization performance of cyanate ester resin can improve its thermal conductivity to a certain extent, but it also faces some challenges and limitations. First, improving the crystallization performance may cause the melting point of the resin to increase, increasing processing difficulty and cost. Secondly, the improvement of the crystallization performance may reduce the fluidity of the resin, affecting the processing process. Furthermore, changes in mechanical properties are a factor to consider. Increasing crystallinity may increase the rigidity and strength of the resin, but reduce its toughness and impact strength. Finally, increasing crystallinity may increase the resin's shrinkage, making it difficult for applications requiring high precision. To address these issues, it is necessary to develop a thermosetting resin and its preparation process for electronic component mounting that exhibits high thermal conductivity to meet the requirements of thermosetting resins for electronic component mounting. Summary of the Invention

[0004] The purpose of the present invention is to provide a thermosetting resin for fixing electronic components and a preparation process thereof, so as to solve the problem that the current thermosetting resin has insufficient thermal conductivity.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: The thermosetting resin for fixing electronic components comprises the following components, calculated in parts by weight: 50 to 75 parts of modified cyanate resin, 10 to 30 parts of surface-modified three-dimensional network aluminum nitride thermal conductive filler, and 3 to 8 parts of curing agent.

[0006] Furthermore, the modified cyanate ester resin is prepared as follows: 100 parts by weight of bisphenol A cyanate ester resin, 4 to 10 parts of fluorine-containing organic matter, 5 to 12 parts of silicon-containing organic matter and 10 to 20 parts of dimethylformamide are added to a reaction kettle, mixed and stirred at 120 to 160° C. for 2 to 4 hours, and then cooled.

[0007] Furthermore, the fluorine-containing organic compound is hexafluorobisphenol A diacrylate or perfluorostyrene.

[0008] Furthermore, the silicon-containing organic compound is methylphenyl silicone resin or aminosilane.

[0009] Furthermore, the preparation method of the surface-modified three-dimensional network aluminum nitride thermal conductive filler is as follows: 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 5 to 10 parts of γ-glycidyloxypropyltrimethoxysilane, 2 to 5 parts of organic salt and 40 to 60 parts of acetone are added to a reactor in sequence by weight, and then reacted for 2 to 6 hours. During the reaction, acetic acid is used to adjust the pH to 5 to 7, and then the surface-modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.

[0010] Furthermore, the organic salt is sodium oxalate or sodium succinate.

[0011] Furthermore, the three-dimensional network aluminum nitride thermal conductive filler is composed of micron-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial pattern.

[0012] Furthermore, the preparation method of the three-dimensional network aluminum nitride thermal conductive filler is as follows: 40 to 80 parts of aluminum nitride whiskers, 9 to 18 parts of aluminum oxide powder, 3 to 6 parts of carbon powder and 0.2 to 0.8 parts of nickel nitrate are mixed evenly by weight, and then heat treated at 1200 to 1400°C for 2 to 6 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.

[0013] Furthermore, the mass ratio of the aluminum oxide powder to the carbon powder is 3:(1~2).

[0014] Furthermore, the curing agent is 2,2'-diallylbisphenol A or triethylenetetramine.

[0015] The present invention also provides a process for preparing a thermosetting resin for fixing electronic components, comprising: According to the weight ratio, the modified cyanate resin and the surface modified three-dimensional network aluminum nitride thermal conductive filler are added to the mixer in sequence and stirred at a stirring speed of 150~300rpm and a stirring time of 60~120min. Then, the curing agent is added and continued to be fully stirred. Then, it is poured into a preheated mold, and then placed in a vacuum defoaming machine for defoaming treatment, and then placed in a vacuum drying oven for staged curing treatment. The staged curing treatment is first heated and cured at 80°C for 2h, then heated and cured at 120°C for 2h, then heated and cured at 160°C for 2h, then heated and cured at 180°C for 2h, and then heated and cured at 220°C for 2h, and finally treated at 240°C for 2~4h to obtain a thermosetting resin for fixing electronic components.

[0016] The purpose of modifying cyanate ester resin with fluorinated organic compounds and silicon-containing groups is to optimize the resin's molecular structure, reduce heat conduction resistance, and thus improve its thermal conductivity, making it more suitable for applications requiring efficient heat conduction, such as electronic packaging. Furthermore, in terms of mechanical properties, the fluorinated organic compounds and silicon-containing groups enhance the resin's hardness and durability, improving its impact and fatigue resistance.

[0017] The thermally conductive filler of the present invention is a three-dimensional network aluminum nitride structure with the following advantages. First, the three-dimensional network aluminum nitride structure is composed of micron-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires. The aluminum nitride whiskers have a large surface area and heat conduction path, which can effectively conduct heat energy, while the aluminum nitride nanowires have a smaller scale and higher thermal conductivity. By combining these two, an efficient heat conduction channel can be formed in the thermally conductive material, thereby improving the thermal conductivity of the material. In addition, the divergent structure of the aluminum nitride nanowires in the present invention also has advantages. The divergent structure provides more heat conduction paths and channels, which can more effectively conduct heat energy. This structure can increase the contact area between the thermally conductive filler and the matrix material, thereby improving the thermal conductivity efficiency. By in-situ growing aluminum nitride nanowires, the bonding between the whiskers and the nanowires can be increased, further improving the thermal conductivity. Finally, the divergent network of aluminum nitride nanowires avoids the agglomeration of nanowires. In summary, the three-dimensional network aluminum nitride structure used in the present invention has high thermal conductivity. It is composed of micron-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires, and the combination of the two is increased by in situ growth. The divergent structure of the aluminum nitride nanowires also has the advantage of providing more heat conduction paths and channels, further improving thermal conductivity and heat conduction efficiency.

[0018] The present invention aims to improve the compatibility and bonding between aluminum nitride and cyanate resin by surface modification of thermally conductive fillers, respectively using γ-glycidyloxypropyltrimethoxysilane and sodium oxalate or sodium succinate, and promote the crystallization of cyanate resin by sodium oxalate or sodium succinate, thereby achieving improved thermal conductivity and good toughness matching for amorphous and crystalline cyanate resins. Specifically, the modification treatment with γ-glycidyloxypropyltrimethoxysilane can increase the compatibility and bonding between the filler and the cyanate resin. The modified surface provides more interaction sites, enhances the adhesion between the filler and the resin, thereby enhancing the bonding ability between them and improving thermal conductivity. In addition, the introduction of sodium oxalate or sodium succinate can promote the crystallization process of the cyanate resin. Sodium oxalate or sodium succinate has a catalytic effect, which can improve the orderly arrangement of resin molecules and the crystallization rate, thereby enhancing the crystallization performance of the resin. By introducing sodium oxalate or sodium succinate on the surface of the thermally conductive filler, a crystalline cyanate resin can be formed on the surface. This crystalline resin has a fast heat conduction channel, which is beneficial to improving thermal conductivity. At the same time, it avoids the crystalline cyanate resin from being evenly distributed in the matrix, achieving a good toughness match. Therefore, the present invention achieves a synergistic improvement in mechanical properties and thermal conductivity by surface-modifying the thermally conductive filler and using γ-glycidyloxypropyltrimethoxysilane and sodium oxalate or sodium succinate respectively. By increasing the compatibility and bonding force of aluminum nitride and cyanate resin and promoting the crystallization of cyanate resin, the thermally conductive filler can be provided with excellent thermal conductivity and a good toughness match.

[0019] Beneficial effects The present invention modifies cyanate ester resins using fluorine-containing organic compounds and silicon-containing groups to improve their thermal conductivity and mechanical properties, making them more suitable for applications requiring efficient heat conduction. This modification optimizes the resin's molecular structure, reduces thermal conductivity resistance, improves thermal conductivity, and enhances its hardness, durability, impact resistance, and fatigue resistance. Furthermore, a three-dimensional network of aluminum nitride (AN) structures is used as a thermally conductive filler, containing micron-scale AN whiskers and nanometer-scale AN nanowires, with in-situ growth enhancing the bonding between the two. This unique structure provides more thermal conduction pathways and channels, further improving thermal conductivity and efficiency. Furthermore, surface modification of the thermally conductive filler using γ-glycidoxypropyltrimethoxysilane and sodium oxalate or sodium succinate enhances the compatibility and bonding between the AN and cyanate resins. Sodium oxalate or sodium succinate also promotes crystallization of the cyanate resin, thereby improving thermal conductivity and achieving a good match between the strength and toughness of the amorphous and crystalline cyanate resins. In summary, this invention successfully overcomes the shortcomings of conventional thermosetting resins in terms of insufficient thermal conductivity and mechanical properties by modifying cyanate ester resins with fluorinated organic compounds and silicon-containing groups, and by preparing a three-dimensional network of thermally conductive fillers. This approach achieves a synergistic improvement in both thermal and mechanical properties. The modified cyanate ester resin exhibits excellent thermal conductivity and a good balance of strength and toughness, making it suitable for applications requiring both efficient thermal conduction and superior mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a morphology image of the three-dimensional network aluminum nitride thermal conductive filler prepared in Example 1 of the present invention; Figure 2 This is an XRD phase analysis diagram of the three-dimensional network aluminum nitride thermal conductive filler prepared in Example 1 of the present invention; Figure 3 This is the XRD phase analysis diagram of the thermosetting resin for fixing electronic components prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] To make the objectives, technical solutions and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.

[0022] Unless otherwise specified, the operations in the examples were performed under conventional conditions or those recommended by the manufacturer. The reagents and instruments used, unless the manufacturer is indicated, are commonly available on the market. Any portion not mentioned in the technical content of the present invention will be handled with reference to the prior art. Unless otherwise specified, the following examples and comparative examples were run in parallel and used the same processing steps and parameters.

[0023] Table 1 below shows the reagents required for the examples and the corresponding purchasing companies: Table 1 Reagents required for the examples and corresponding purchasing companies

[0024] Example 1 Thermosetting resin for fixing electronic components comprises the following components in parts by weight: 50 parts of modified cyanate resin, 10 parts of surface-modified three-dimensional network aluminum nitride thermal conductive filler, and 3 parts of curing agent.

[0025] The modified cyanate resin is prepared as follows: 100 parts by weight of bisphenol A cyanate resin, 4 parts of fluorine-containing organic matter, 5 parts of silicon-containing organic matter and 10 parts of dimethylformamide are added to a reaction kettle, mixed and stirred at 120° C. for 2 hours, and then cooled.

[0026] The above-mentioned fluorine-containing organic compound is hexafluorobisphenol A diacrylate; the silicon-containing organic compound is methylphenyl silicone resin.

[0027] The preparation method of the above-mentioned surface-modified three-dimensional network aluminum nitride thermal conductive filler is as follows: 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 5 parts of γ-glycidyloxypropyltrimethoxysilane, 2 parts of organic salt and 40 parts of acetone are added to a reactor in sequence by weight, and then reacted for 2 hours. During the reaction, the pH is adjusted to 5 with acetic acid, and then the surface-modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.

[0028] The above-mentioned organic salt is sodium oxalate.

[0029] The three-dimensional network aluminum nitride thermal conductive filler is composed of micron-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.

[0030] The preparation method of the above-mentioned three-dimensional network aluminum nitride thermal conductive filler is as follows: 40 parts of aluminum nitride whiskers, 9 parts of aluminum oxide powder, 3 parts of carbon powder and 0.2 parts of nickel nitrate are mixed evenly by weight, and then heat treated at 1200°C for 2 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.

[0031] The mass ratio of the above-mentioned aluminum oxide powder to carbon powder is 3:1.

[0032] The above-mentioned curing agent is 2,2'-diallyl bisphenol A.

[0033] The present invention also provides a process for preparing a thermosetting resin for fixing electronic components: According to the weight ratio, the modified cyanate resin and the surface modified three-dimensional network aluminum nitride thermal conductive filler are added to the mixer in turn and stirred at a stirring speed of 150 rpm for 60 minutes. Then, the curing agent is added and continued to be fully stirred. Then, it is poured into a preheated mold, placed in a vacuum defoamer for defoaming treatment, and then placed in a vacuum drying oven for staged curing treatment. The staged curing treatment is first heated and cured at 80°C for 2 hours, then heated and cured at 120°C for 2 hours, then heated and cured at 160°C for 2 hours, then heated and cured at 180°C for 2 hours, and then heated and cured at 220°C for 2 hours. Finally, it is treated at 240°C for 2 hours to obtain a thermosetting resin for fixing electronic components.

[0034] The structural composition and phase characteristics of the prepared three-dimensional network aluminum nitride thermal conductive filler were obtained through scanning electron microscopy (SEM) morphology observation, X-ray diffraction (XRD) phase analysis and other characterization methods: Figure 1 Morphological analysis shows that the three-dimensional network aluminum nitride thermal conductive filler prepared in Example 1 presents a three-dimensional network structure constructed by interweaving micron-scale aluminum nitride whiskers and nanoscale aluminum nitride nanowires, which provides an excellent structural basis for it to serve as a thermal conductive path. Figure 2 The phase analysis results of the three-dimensional network aluminum nitride thermal conductive filler show that it contains only a single phase of aluminum nitride and no other impurities. Figure 3 Thermosetting resin for fixing electronic components prepared in Example 1 The XRD phase analysis diagram of the thermal conductive resin shows that in addition to the aluminum nitride phase, it also contains crystalline cyanate resin. Its broad peak proves that it is nanocrystalline, proving that the surface-modified three-dimensional network aluminum nitride thermal conductive filler can promote the crystallization of cyanate resin, thereby improving the mechanical properties and thermal conductivity.

[0035] Example 2 Thermosetting resin for fixing electronic components comprises the following components in parts by weight: 60 parts of modified cyanate resin, 15 parts of surface-modified three-dimensional network aluminum nitride thermal conductive filler, and 4 parts of curing agent.

[0036] The preparation method of the modified cyanate ester resin is as follows: 100 parts by weight of bisphenol A cyanate ester resin, 5 parts of fluorine-containing organic matter, 6 parts of silicon-containing organic matter and 14 parts of dimethylformamide are added to a reaction kettle, mixed and stirred at 130° C. for 3 hours, and then cooled.

[0037] The above-mentioned fluorine-containing organic compound is perfluorostyrene.

[0038] The above-mentioned silicon group-containing organic compound is aminosilane.

[0039] The preparation method of the above-mentioned surface-modified three-dimensional network aluminum nitride thermal conductive filler is as follows: 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 6 parts of γ-glycidyloxypropyltrimethoxysilane, 3 parts of organic salt and 45 parts of acetone are added to a reactor in sequence by weight, and then reacted for 4 hours. During the reaction, the pH is adjusted to 5.5 with acetic acid, and then the surface-modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.

[0040] The above-mentioned organic salt is sodium succinate.

[0041] The three-dimensional network aluminum nitride thermal conductive filler is composed of micron-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.

[0042] The preparation method of the above-mentioned three-dimensional network aluminum nitride thermal conductive filler is as follows: 50 parts of aluminum nitride whiskers, 12 parts of aluminum oxide powder, 4 parts of carbon powder and 0.4 parts of nickel nitrate are mixed evenly by weight, and then heat treated at 1300°C for 4 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.

[0043] The mass ratio of the above-mentioned aluminum oxide powder to carbon powder is 3:1.

[0044] The curing agent is triethylenetetramine.

[0045] The present invention also provides a preparation process of a thermosetting resin for fixing electronic components, which is the same as that in Example 1 and will not be repeated here.

[0046] Example 3 Thermosetting resin for fixing electronic components comprises the following components in parts by weight: 60 parts of modified cyanate resin, 20 parts of surface-modified three-dimensional network aluminum nitride thermal conductive filler, and 5 parts of curing agent.

[0047] The modified cyanate resin is prepared as follows: 100 parts by weight of bisphenol A cyanate resin, 8 parts by weight of fluorine-containing organic matter, 10 parts by weight of silicon-containing organic matter and 15 parts by weight of dimethylformamide are added to a reaction kettle, mixed and stirred at 140° C. for 3 hours, and then cooled.

[0048] The above-mentioned fluorine-containing organic compound is perfluorostyrene.

[0049] The above-mentioned silicon group-containing organic compound is aminosilane.

[0050] The preparation method of the above-mentioned surface-modified three-dimensional network aluminum nitride thermal conductive filler is as follows: 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 8 parts of γ-glycidyloxypropyltrimethoxysilane, 4 parts of organic salt and 50 parts of acetone are added to a reactor in sequence by weight, and then reacted for 5 hours. During the reaction, acetic acid is used to adjust the pH to 5.5, and then the surface-modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.

[0051] The above-mentioned organic salt is sodium succinate.

[0052] The three-dimensional network aluminum nitride thermal conductive filler is composed of micron-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.

[0053] The preparation method of the above-mentioned three-dimensional network aluminum nitride thermal conductive filler is as follows: 70 parts of aluminum nitride whiskers, 15 parts of aluminum oxide powder, 5 parts of carbon powder and 0.6 parts of nickel nitrate are mixed evenly by weight, and then heat treated at 1300°C for 5 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.

[0054] The mass ratio of the above-mentioned aluminum oxide powder to carbon powder is 3:1.

[0055] The curing agent is triethylenetetramine.

[0056] The present invention also provides a preparation process of a thermosetting resin for fixing electronic components, which is the same as that in Example 1 and will not be repeated here.

[0057] Example 4 Thermosetting resin for fixing electronic components comprises the following components in parts by weight: 75 parts of modified cyanate resin, 30 parts of surface-modified three-dimensional network aluminum nitride thermal conductive filler, and 8 parts of curing agent.

[0058] The preparation method of the modified cyanate ester resin is as follows: 100 parts by weight of bisphenol A cyanate ester resin, 10 parts by weight of fluorine-containing organic matter, 12 parts by weight of silicon-containing organic matter and 20 parts by weight of dimethylformamide are added to a reaction kettle, mixed and stirred at 160° C. for 4 hours, and then cooled.

[0059] The above-mentioned fluorine-containing organic compound is perfluorostyrene.

[0060] The above-mentioned silicon group-containing organic compound is aminosilane.

[0061] The preparation method of the above-mentioned surface-modified three-dimensional network aluminum nitride thermal conductive filler is as follows: 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 10 parts of γ-glycidyloxypropyltrimethoxysilane, 5 parts of organic salt and 60 parts of acetone are added to a reactor in sequence by weight, and then reacted for 6 hours. During the reaction, the pH is adjusted to 7 with acetic acid, and then the surface-modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.

[0062] The above-mentioned organic salt is sodium oxalate or sodium succinate.

[0063] The three-dimensional network aluminum nitride thermal conductive filler is composed of micron-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.

[0064] The preparation method of the above-mentioned three-dimensional network aluminum nitride thermal conductive filler is as follows: 80 parts of aluminum nitride whiskers, 18 parts of aluminum oxide powder, 6 parts of carbon powder and 0.8 parts of nickel nitrate are mixed evenly by weight, and then heat treated at 1400°C for 6 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.

[0065] The mass ratio of the above-mentioned aluminum oxide powder to carbon powder is 3:2.

[0066] The curing agent is triethylenetetramine.

[0067] The present invention also provides a preparation process of a thermosetting resin for fixing electronic components, which is the same as that in Example 1 and will not be repeated here.

[0068] Example 5 The method is basically the same as Example 1, except that the amount of the surface-modified three-dimensional network aluminum nitride thermal conductive filler is 30 parts.

[0069] Comparative Example 1 The method is basically the same as Example 1, except that the thermosetting resin does not contain the surface-modified three-dimensional network aluminum nitride thermal conductive filler.

[0070] Comparative Example 2 The method is basically the same as Example 1, except that the preparation of the modified cyanate ester resin does not include fluorine-containing organic matter.

[0071] Comparative Example 3 The method is basically the same as Example 1, except that the preparation of the modified cyanate ester resin does not include organic matter containing silicon groups.

[0072] Comparative Example 4 It is basically the same as Example 1, except that the three-dimensional network aluminum nitride thermal conductive filler has not been subjected to surface modification treatment.

[0073] Comparative Example 5 It is basically the same as Example 1, except that the aluminum nitride whiskers and aluminum nitride are added separately in an external manner, so there is no in-situ strong interface bonding between the two, and the two are not connected to form a three-dimensional heat conduction network.

[0074] Performance testing: The peel strength is tested according to IPC-TM-650 method.

[0075] Thermal conductivity is tested according to ASTM-D-5470 method.

[0076] The peel strength and thermal conductivity of the thermosetting resins of Examples 1 to 5 and Comparative Examples 1 to 5 are summarized in Table 2.

[0077] Table 2 Performance test table of thermosetting resins of Examples 1 to 5 and Comparative Examples 1 to 5

[0078] The main difference between Example 1 and Comparative Example 1 is whether the thermosetting resin contains a surface-modified three-dimensional network aluminum nitride thermal conductive filler. From Table 2, it can be seen that the surface-modified three-dimensional network aluminum nitride thermal conductive filler can improve the mechanical properties and thermal conductivity of the thermosetting resin.

[0079] The main difference between Example 1 and Comparative Examples 2 and 3 is whether the thermosetting resin uses a modified resin matrix of fluorine-containing organic matter and silicon-containing organic matter. It can be seen that these two can significantly improve the molecular network structure of the resin matrix, which helps to optimize the thermal conductivity and mechanical properties of the thermosetting resin.

[0080] The main difference between Example 1 and Comparative Example 4 lies in whether the three-dimensional network thermally conductive filler is surface-modified. It can be seen that the surface-modified thermally conductive filler can enhance its bonding with the matrix resin and promote the crystallization of the nanocrystalline cyanate ester resin, thereby improving mechanical properties and thermal conductivity.

[0081] The primary difference between Example 1 and Comparative Example 5 lies in whether the micron-scale aluminum nitride exhibits strong interfacial bonding, and thus whether both construct a three-dimensional thermal conductivity path. Table 2 shows that the micron-scale aluminum nitride whiskers and nanometer-scale nanowires construct a three-dimensional network structure, which can form a rapid thermal conductivity path and improve mechanical properties.

[0082] In summary, the present invention achieves a synergistic improvement in mechanical properties and thermal conductivity by using a modified resin matrix prepared from fluorine-containing organic matter and silicon-containing organic matter, as well as a design of a three-dimensional network aluminum nitride thermal conductive filler and its surface modification, which can significantly improve the mechanical properties and thermal conductivity of thermosetting resins.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that any equivalent structural transformations made within the scope of the present invention using the contents of the present invention's description and drawings should be included within the scope of protection of the claims of the present invention.

Claims

1. A thermosetting resin for fixing electronic components, characterized in that: The composition comprises the following components in parts by weight: 50-75 parts of modified cyanate resin, 10-30 parts of surface modified three-dimensional network aluminum nitride thermal conductive filler, and 3-8 parts of curing agent; The modified cyanate resin preparation method is as follows: by weight, 100 parts of bisphenol A cyanate resin, 4-10 parts of fluorine-containing organic matter, 5-12 parts of silicon-containing organic matter and 10-20 parts of dimethylformamide are added into a reaction kettle, mixed and stirred at 120-160° C. for 2-4 hours, and cooled; The preparation method of the surface modified three-dimensional network aluminum nitride thermal conductive filler is as follows: by weight, 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 5-10 parts of γ-glycidyloxypropyltrimethoxysilane, 2-5 parts of organic salt and 40-60 parts of acetone are added to a reaction kettle in sequence, and then reacted for 2-6 hours, and acetic acid is used to adjust the pH to 5-7 during the reaction, and then filtered, washed and dried to obtain the surface modified three-dimensional network aluminum nitride thermal conductive filler; The organic salt is sodium oxalate or sodium succinate; The three-dimensional network aluminum nitride thermal conductive filler is composed of micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape; The curing agent is 2,2'-diallyl bisphenol A or triethylenetetramine.

2. The thermosetting resin for fixing electronic components according to claim 1, characterized in that: The fluorine-containing organic compound is hexafluorobisphenol A diacrylate or perfluorostyrene.

3. The thermosetting resin for fixing electronic components according to claim 1, characterized in that: The silicon-containing organic matter is methylphenyl silicone resin or aminosilane.

4. The thermosetting resin for fixing electronic components according to claim 1, characterized in that: The preparation method of the three-dimensional network aluminum nitride thermal conductive filler is as follows: by weight, 40 to 80 parts of aluminum nitride whiskers, 9 to 18 parts of aluminum oxide powder, 3 to 6 parts of carbon powder and 0.2 to 0.8 parts of nickel nitrate are evenly mixed, and then heat treated at 1200 to 1400° C. for 2 to 6 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.

5. The thermosetting resin for fixing electronic components according to claim 4, characterized in that: The mass ratio of alumina powder to carbon powder is 3:(1~2).

6. A process for preparing a thermosetting resin for fixing electronic components, which is used to prepare the thermosetting resin for fixing electronic components according to any one of claims 1 to 5, characterized in that: According to the weight ratio, the modified cyanate resin and the surface modified three-dimensional mesh aluminum nitride thermal conductive filler are added to the mixer in sequence for stirring at a stirring speed of 150-300 rpm for 60-120 min, and then the curing agent is added to continue to be fully stirred, and then poured into a preheated mold, and then placed in a vacuum defoaming machine for defoaming treatment, and then placed in a vacuum drying oven for staged curing treatment. The staged curing treatment is first heated and cured at 80°C for 2h, then heated and cured at 120°C for 2h, then heated and cured at 160°C for 2h, then heated and cured at 180°C for 2h, and then heated and cured at 220°C for 2h, and finally treated at 240°C for 2-4h to obtain a thermosetting resin for fixing electronic components.

Citation Information

Patent Citations

  • A modified cyanate resin thermally conductive composite material and preparation method thereof

    CN104231624B

  • Organosilane modified bisphenol A cyanate ester resin and preparation method thereof

    CN101456953A

  • Zinc oxide whisker / graphene nanosheet synergistically modified cyanate ester resin heat conduction composite and preparation method thereof

    CN104312147A

  • Flame resistant, low-temperature curing cyanate resin having improved properties

    EP1854827A1

  • Resin composition comprising cyanate ester compound and cured product thereof

    JP2017008236A